Perspektif Hak Asasi Manusia dan Landasan Yuridis terkait Praktik Abortus Provocatus di Indonesia - Salma Agustina; Handar Subhandi Bakhtiar (Universitas Muhammadiyah Yogyakarta, 2023)
In medically, abortion refers to actions on a fetus that cannot survive outside the womb by stopping and removing the fetus.The purpose of this study is to understand the view of human rights and the juridical basis for the practice of abortion provocatus in Indonesia. As for the perspective of human rights, in order to be able to find out what rights are attached to mothers and children to this practice in order to determine the responsibilities of various parties related to the rules based on positive law. Furthermore, to comprehend the regulations that oversee the implementation of abortus provocatus so that they can know how they are held accountable for the types of abortion that are included in Abortus Provocatus based on positive law in Indonesia. The results obtained in this study indicate that according to the view of human rights (HAM), in the practice of abortion provocatus there are 2 rights that are discussed, namely the right to life for the fetus and the right to health for the mother. Basically abortion in any form is strictly prohibited because it is included in the deprivation of the right to life. However, the problem becomes different when the gestation period displays signs of a healthcare crisis that could jeopardize the well-being of the mother.. Meanwhile, there are 2 rules that form the juridical basis for the practice of provocatus abortion in Indonesia, namely the Criminal Code and the Health Law. In the Criminal Code, abortion is strictly prohibited and is a crime. Meanwhile, there is an exception to the prohibition on abortion provocatus which is regulated in the Health Law, namely if pregnancy occurs in a woman who is a victim of rape and the pregnancy has indications of a medical emergency